2007
DOI: 10.1007/s10509-007-9385-z
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Planetary Interiors in Laser Based Experiments Using Shockless Compression

Abstract: X-ray diffraction is a widely used technique for measuring the crystal structure of a compressed material. Recently, short pulse x-ray sources have been used to measure the crystal structure in-situ while a sample is being dynamically loaded. To reach the ultra high pressures that are unattainable in static experiments at temperatures lower than using shock techniques, shockless quasi-isentropic compression is required. Shockless compression has been demonstrated as a successful means of accessing high pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Static-compression diamond-anvil-cell experiments have given us a great deal of information about water ice up to pressures of 0.21 TPa [4][5][6], but this is far below the highest pressures to which water is subjected within planets. Shock wave experiments can reach much higher pressures, and sample precompression [7,8] and ramped compression [9,10] techniques can reduce the resulting temperatures to those more appropriate for planetary science.…”
mentioning
confidence: 99%
“…Static-compression diamond-anvil-cell experiments have given us a great deal of information about water ice up to pressures of 0.21 TPa [4][5][6], but this is far below the highest pressures to which water is subjected within planets. Shock wave experiments can reach much higher pressures, and sample precompression [7,8] and ramped compression [9,10] techniques can reduce the resulting temperatures to those more appropriate for planetary science.…”
mentioning
confidence: 99%
“…That view was challenged recently, when a cagelike diamondoid "N10" structure (space group I43m) was found to be more stable than any other candidate above 263 GPa [31]. Recently, the melting behavior of nitrogen and phases beyond cg-N have also been investigated [10][11][12]30].Recently, dynamical shock wave [36][37][38] and ramped compression experiments [39][40][41] have increasingly been used to investigate materials at TPa pressures. Even more extreme conditions are attainable today in laser ignition experiments [42] and laser-induced microexplosions [43].…”
mentioning
confidence: 99%
“…Materials under terapascal pressures are of great interest in planetary science, for example, the pressure at the center of Jupiter is estimated to be about 7 TPa [24]. Recent progress in dynamical shock wave [24][25][26] and ramped compression experiments [27,28] has demonstrated that the terapascal pressure regime is becoming much more accessible.The use of DFT computations combined with searching methods has provided a new route for predicting the structures and energetics of high-pressure phases [23,29,30]. A very recent study of phase transitions, melting, and chemical reactivity in CO 2 found it to dissociate into carbon and oxygen above 33 GPa and 1720 K [31], which adds further motivation for studying pure oxygen at high pressures.…”
mentioning
confidence: 99%
“…Materials under terapascal pressures are of great interest in planetary science, for example, the pressure at the center of Jupiter is estimated to be about 7 TPa [24]. Recent progress in dynamical shock wave [24][25][26] and ramped compression experiments [27,28] has demonstrated that the terapascal pressure regime is becoming much more accessible.…”
mentioning
confidence: 99%